Sperm Competitive Ability in Drosophila melanogaster Associated With Variation in Male Reproductive Proteins - Fiumera, Anthony C. (Genetics Society of America, 2005)
Multiple mating by females establishes the opportunity for postcopulatory sexual selection favoring males whose sperm is preferentially employed in fertilizations. Here we use natural variation in a wild population of Drosophila melanogaster to investigate the genetic basis of sperm competitive ability. Approximately 101 chromosome 2 substitution lines were scored for components of sperm competitive ability (P1′, P2′, fecundity, remating rate, and refractoriness), genotyped at 70 polymorphic markers in 10 male reproductive genes, and measured for transcript abundance of those genes. Permutation tests were applied to quantify the statistical significance of associations between genotype and phenotype. Nine significant associations were identified between polymorphisms in the male reproductive genes and sperm competitive ability and 13 were identified between genotype and transcript abundance, but no significant associations were found between transcript abundance and sperm competitive ability. Pleiotropy was evident in two genes: a polymorphism in Acp33A associated with both P1′ and P2′ and a polymorphism in CG17331 associated with both elevated P2′ and reduced refractoriness. The latter case is consistent with antagonistic pleiotropy and may serve as a mechanism maintaining genetic variation.